Functional lingual thyroid in an adolescent female: a case report and brief literature review (Bangladesh Journal of Medical Science, 2011)
Background: Lingual thyroid is a rare clinical entity that represents faulty migration of normal thyroid gland. It commonly presents as a benign mass found at the junction of the anterior two-thirds and posterior one-third of the tongue. Although usually asymptomatic, glandular hypertrophy can cause dysphonia, dysphagia, bleeding, or stridor at any time from infancy through adulthood. We report a case that we encountered, discuss the diagnosis and its management, and review the literature. An otherwise asymptomatic 14 year-old girl presented with a posterior tongue mass that had been present since childhood but was never investigated. She was clinically and biochemically euthyroid, with normal thyroid function tests. Physical examination revealed a smooth, globular mass occupying the whole tongue base and valleculae. The epiglottis was slightly displaced posteriorly but the laryngeal inlet was patent. A 99mTcradioisotope scan showed accumulation of tracer in the tongue base and no uptake in the neck. MRI revealed a 1.8-cm diameter soft tissue mass in the posterior part of the tongue. To date she has not required suppressive therapy or surgical intervention. Conclusions: Treatment of lingual thyroid depends on patient symptoms. Most importantly, patients should be followed at regular intervals and educated on the possibility of developing complications. Key words: Lingual thyroid, ectopic thyroid, thyroid gland. DOI: http://dx.doi.org/10.3329/bjms.v10i3.8370 BJMS 2011; 10(3): 216-219